Planting Green: Potential Benefits and Disadvantages of Planting Corn into Live Cereal Rye Cover Crop - A. Correira; P. Tomlinson; D. Presley (Kansas Agricultural Experiment Station Research Reports, 2023)
Although cover crops are typically terminated 2–4 weeks prior to cash crop planting, there may be situations where late-burndown or planting into a living cover crop (planting green) may be necessary or even beneficial. This experiment investigated the effect of cover crop termination date on corn (Zea mays) yield and the presence of beneficial insects. Three different termination dates were tested: 4 weeks prior to planting (brown), 7 to 14 days prior to planting (green-brown), and at planting (green), as well as a check treatment with no cover crop planted. The site year by termination date interaction was significant for cover crop biomass and thus each year was analyzed separately. Preliminary results of sentinel prey assessments indicate no significant difference in the presence of beneficial insects in the systems. However, there was a significant yield decrease in treatments where corn was planted into a green cover crop in both 2021 and 2022. Cover crop yields in 2022 were 50% lower than those observed in 2021. The control and planting brown treatments resulted in significantly higher yields than the planting green-brown and green treatments in 2022.
Keywords: planting green; cereal rye; cover crops; no-till; pest control